Analisis Kemampuan Pemecahan Masalah Matematis Siswa dengan Menerapkan Model PjBL Berbantuan E-modul Lubuk Etnomatematika - Mardhiyah, Umi; Wanabuliandari, Savitri; Bintoro, Henry Suryo (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The preliminary study at SMP Negeri 5 Pati obtained an average score of 33.44. This shows that the students' mathematical problem solving ability is still low. The purpose of this study was to analyze the average mathematical problem solving ability of students who received Project Based Learning learning assisted by the Lubukethnomathematics e-module whether they could achieve the KKM score. The research method used was quantitative, quasi-experimental design, the nonequivalent pretest-posttest control group design. Sampling with purposive sampling technique. Analysis of the data used, including normality test, homogeneity test, and one independent sample t test. The results showed that the average mathematical problem solvingability of students who were taught the PjBL model assisted by the Lubukethnomathematics e-module was more than 75. The conclusion of this study is that the average mathematical problem solving ability of students can achieve the KKM score